Impact of local revenue (PAD) and transfer funds on regional financial independence in North Sumatra province: english - Rahmat Hidayat; Erlina, Erlina; Badaruddin, Badaruddin (SEAN Institute, 2024)
This study aims to analyze the influence of Local Revenue (PAD) and Transfer Funds on the level of regional financial independence in North Sumatra Province. The research employs a combined quantitative and qualitative approach, with a focus on key variables such as Local Revenue, Transfer Funds, and the level of financial independence. Data was collected from publications by the Central Statistics Agency (BPS) and related sources on regional income, fund allocation, and regional development for the period from 2017 to 2021. The findings reveal that Local Revenue (PAD) has a positive and significant impact on the level of regional financial independence, while Transfer Funds exhibit a significant negative influence. This implies that an increase in Local Revenue enhances financial independence, while reliance on Transfer Funds tends to diminish it. These insights are relevant for regional financial planning and development strategies in North Sumatra Province.